Privatising Security Post-Arab Uprisings - Moussa, Engy (Cranfield University, 2020)
Since the 2010-2011 uprisings, several Arab countries have witnessed considerable expansion of the private security industry. Acknowledging that public security institutions have been integral to state power and regime stability in the region, this research investigates how increased privatization and outsourcing of security contribute to the survival of authoritarian rule in different Arab countries.The research essentially argues that privatizing and outsourcing security effectively fits into a broader scheme of authoritarian regime adaptation. It serves to enhance regime security by providing alternative agents and strategies for social control. Meanwhile, it offers new venues to expand regime interests by nurturing broad authoritarian coalitions and attaching the interests of diverse social groups to regime survival.
Keywords: 'DSDS20 3MT'; 'DSDS20'; 'Private security'; 'Middle East'; 'Authoritarianism'; 'Private Policing and Security Services'